2015
DOI: 10.14260/jemds/2015/1331
|View full text |Cite
|
Sign up to set email alerts
|

A Double - Blind, Placebo - Controlled, Randomized Study Comparing Quetiapine With Placebo, Along With Oral Naltrexone, in the Treatment of Opioid Dependent Patients

Abstract: AIM:The aim of the study is to compare quetiapine with placebo along with oral naltrexone in the treatment of opioid dependent patients. We conducted the study as opioid dependence is steadily increasing in this area and more research is needed to prevent relapse after opioid detoxification. SETTINGS AND DESIGN: It is a double blind placebo controlled , randomized study that was conducted in department of psychiatry, de addiction unit (Sri Guru Ram Das Institute of Medical Sciences & Research, Sri Amritsar) ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Relapse rate after opioid detoxification ranges from 72% to 88% after 12 to 36 months, despite multidisciplinary endeavors, although a 6-month controlled study showed lower relapse rate (32% to 70%) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Relapse rate after opioid detoxification ranges from 72% to 88% after 12 to 36 months, despite multidisciplinary endeavors, although a 6-month controlled study showed lower relapse rate (32% to 70%) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Relapse rate after opioid detoxification ranges from 72 to 88% after 12–36 months, despite multidisciplinary endeavors, though a six-month controlled study has shown lower relapse rate (32–70%) [ 1 , 2 ]. Improvement in this rate can be done by a better understanding of pretreatment risk factors, including patient characteristics, associated with relapse after inpatient detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to administer naltrexone an individual must first complete a 10-day period of opioid abstinence, referred to as the “induction hurdle.” This period of abstinence significantly increases the likelihood of experiencing opioid withdrawal symptoms, resulting in a high number of patients that fail to comply with treatment. Relapse to using opioid drugs is seen in 32–70% in patients within six month after treatment initiation and 72 to 88% of patients after 12–36 months (Strain et al 2009 ; Chalana et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%